Serwis informacyjny jako ważny element realizacji misji regionalnych rozgłośni radiowych na przykładzie Radia Olsztyn - Doliwa, Urszula (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2017)
In accordance with the Act on radiophony and television a public broadcaster, such as the regional broadcasters of Polish Radio, is required to fulfil the so-called public mission. One important element of the programme which fulfilling this mission entails is the news bulletin. News bulletins emitted on Polish Radio Olsztyn in selected weeks of 2015 and 2016 are analysed. From this analysis, it emerges that particular attention is paid to this element of the programming in Radio Olsztyn. This is testified to both by the frequency with which bulletins are broadcast – as much as 28 times a day on weekdays, or the number of news items in each bulletin and their wide-ranging character, as well as the large number of journalists involved in the preparation of this scheduled item, the network of correspondents and local studios in Elbląg and Ełk. The radio station is an important source of regional and local information. However, although the method of preparing the information for the bulletins may be described as easy on the ear, their choice is typified by a high degree of conventionalisation.